Severity in the ICD-11 personality disorder model: Evaluation in a Spanish mixed sample - Gutiérrez, Fernando; Aluja, Anton; Rodríguez, Claudia; Gárriz, Miguel; Peri, Josep M.; Gallart, Salvador; Calvo, Natalia; Ferrer, Marc; Gutiérrez-Zotes, Alfonso; Soler, Joaquim; Pascual, Juan Carlos (Frontiers in Psychiatry, 2023)
Severity is the main component of the ICD-11 personality disorder (PD) classification, but pertinent instruments have only recently been developed. We analyzed the psychometric properties of the ICD-11 Personality Disorder Severity scale (PDS-ICD-11) in a mixed sample of 726 community and clinical subjects. We also examined how the different components of the ICD-11 PD system —five trait domains, the borderline pattern specifier, and severity, all of them measured through self-reports— are interconnected and operate together. PDS-ICD-11 properties were adequate and similar to those of the original instrument. However, regressions and factor analyses showed a considerable overlap of severity with the five personality domains and the borderline specifier (72.6%). Bifactor modeling resulted in a general factor of PD (g-PD) that was not equivalent to severity nor improved criterion validity. The whole ICD-11 PD system, i.e., five personality domains, borderline, and severity, explained an average of 43.6% of variance of external measures of well-being, disability, and clinical problems, with severity contributing 4.8%. Suggestions to further improve the ICD-11 PD taxonomy include remodeling the present definition of severity to give more weight to the real-life consequences of traits.